Transform 101 Natural Look Triangle Breast Form Prosthesis - Science History Institute (2021)
TRANSFORM® brand silicone breast forms in size 8 manufactured by Nearly Me Technologies, LLC, a manufacturer of health care products and prostheses, specializing in silicone gel and foam technology. Nearly Me Technologies, LCC created the TRANSFORM® Brand of products in 1999. Nearly Me Technologies, LLC claims to be the first company to design and develop breast forms for the transgender and genderqueer market. TRANSFORM® breast forms are still manufactured in the United States using medical-grade silicone technology.
Keywords: Breast; Silicone rubber; Women's health services; Women--Health and hygiene; Gender expression; Commercial products; Gender nonconformity; Gender identity; Prosthesis; Transgender people